Productivity and efficiency in the health care system with special focus on hospital performance - Medarević, Aleksandar P; Vuković, Dejana (Medicinski podmladak, 2022)
The principle of efficiency calls on all participants in the provision of health care to seek either better results concerning available financial resources or the highest level of health care with the least resources expenditure. The paper presents a review of theoretical productivity and efficiency concepts and their measuring regarding the health care system and the hospitals’ operations. Knowledge of these relationships is essential for the practical implementation of the efficiency principle. The paper also summarizes the results of efficiency studies from comparable, Eastern European systems. Efficiency is a multifactorial phenomenon, for the improvement of which there is a whole range of interventions. The management should implement some of these interventions in the system under their responsibility.
Keywords: benchmarking; health system; healthcare; review; performance assessment